Gamification as a Sustainable Source of Enjoyment During Balance and Gait Exercises - van der Kooij, Katinka; van Dijsseldonk, Rosanne; van Veen, Milou; Steenbrink, Frans; de Weerd, Coen; Overvliet, Krista E. (Frontiers in Psychology, 2019)
We may be motivated to engage in a certain motor activity because it is instrumental to obtaining reward (e.g. money) or because we enjoy the activity, making it intrinsically rewarding. Enjoyment is related to intrinsic motivation which is considered to be a more durable form of motivation. Therefore, many rehabilitation programs aim to increase task enjoyment by adding game elements (‘gamification’). Here we ask how the influence of game elements on motivation develops over time and additionally explore whether enjoyment influences motor performance. We describe two different studies that varied game elements in different exercises. Experiment 1 compared the durability of enjoyment for a gamified and a conventional balance exercise in elderly. Experiment 2 addressed the question whether adding game elements to a gait adaptability exercise enhances the durability of enjoyment and additionally tested whether the game elements influenced movement vigor and accuracy (motor performance). The results show that the game elements enhanced enjoyment. Enjoyment faded over time, but this decrease tended to be less pronounced in gamified exercises. There was no evidence that the game elements affected movement vigor or accuracy.